To be a slave - Lester, Julius (New York Dial Books, 1998)
A compilation, selected from various sources and arranged chronologically, of the reminiscences of slaves and ex-slaves about their experiences from the leaving of Africa through the Civil War and into the early twentieth century.
Keywords: Slaves -- United States -- Quotations; Slaves -- United States -- Social conditions; Slaves -- United States -- Biography